Interplay of Bright Triplet and Dark Excitons Revealed by Magneto‐Photoluminescence of Individual PbS/CdS Quantum Dots. Issue 13 (9th March 2021) - Kim, Younghee; Hu, Zhongjian; Avdeev, Ivan D.; Singh, Ajay; Singh, Amita; Chandrasekaran, Vigneshwaran; Nestoklon, Mikhail O.; Goupalov, Serguei V.; Hollingsworth, Jennifer A.; Htoon, Han
Abstract: A low‐temperature polarization‐resolved magneto‐photoluminescence experiment is performed on individual PbS/CdS core/shell quantum dots (QDs). The experiment enables a direct measurement of the exciton Landé g factor and the anisotropic zero‐field splitting of the lowest emissive bright exciton triplet in PbS/CdS QDs. While anisotropic splittings of individual QDs distribute randomly in 104—325 μeV range, the exciton Landé g factors increase from 0.95 to 2.70 as the emission energy of the QD increases from 1.0 to 1.2 eV. The tight‐binding calculations allow to rationalize these trends as a direct consequence of reducing a cubic symmetry of QD via addition/removal of a few (<70) atoms from the surfaces of the PbS core. Furthermore, it is observed that while right ( σ + ) and left ( σ − ) circularly polarized photoluminescence (PL) peaks split linearly with magnetic field as expected for Zeeman effect, the energy splitting between X and Y linearly polarized PL peaks remains nearly unchanged. The theoretical study reveals rich and complex magnetic field‐induced interplay of bright triplet and dark exciton states explaining this puzzling behavior. These findings fill the missing gaps in the understanding of lead salt QDs and provide foundation for development of classical and quantum light sources operating at telecommunication wavelengths. Abstract : This article reports a single quantum dot, low‐temperature, magneto‐photoluminescence spectroscopy study unmasking the fine structure of the lowest energy exciton states of the PbS quantum dots and the way they interact with light. These findings fill the missing gaps in fundamental understanding and lay down the foundation for development of classical and quantum light source operating at telecommunication wavelengths.